Digital Media Evolution and Public Opinion Formation: Implications for Information Credibility and Social Dynamics - Zulkarnain, Muhamad Amir Bin; Al Hakim, Yusuf Rahman (Bulletin of Science, Technology and Society, 2023)
The development of digital media has fundamentally changed the way society receives information and shape’s public opinion. The transition from traditional media to digital platforms allows for faster, wider and more interactive dissemination of information, but also poses challenges related to credibility, algorithmic bias and the spread of misinformation. This research aims to analyze how media evolution affects communication patterns and public perception in social and political dynamics. Using a literature review method, this research examines various factors that contribute to changes in information consumption patterns, including the role of social media algorithms, digital journalism, and society involvement in content production. The research results show that media evolution has an impact on increasing public engagement in political discourse, and can strengthen polarization and information echo chambers. Media literacy is an important aspect to help people sort out accurate information from biased or misleading ones. In addition, the role of governments, technology companies, and academic institutions is needed to develop policies that ensure transparency and accountability of information. The conclusion of this research emphasizes that understanding the evolution of the media is crucial to maintaining the integrity of information and encouraging healthier public participation in democratic processes and social life. Thus, communication strategies based on ethics and information accuracy must continue to be developed to optimize the role of media in modern society.